2015
DOI: 10.1371/journal.pone.0116800
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Herpes Simplex Virus Induced Stromal Keratitis by a Glycoprotein B-Specific Monoclonal Antibody

Abstract: The increasing incidence of acyclovir (ACV) and multidrug-resistant strains in patients with corneal HSV-1 infections leading to Herpetic Stromal Keratitis (HSK) is a major health problem in industrialized countries and often results in blindness. To overcome this obstacle, we have previously developed an HSV-gB-specific monoclonal antibody (mAb 2c) that proved to be highly protective in immunodeficient NOD/SCID-mice towards genital infections. In the present study, we examined the effectivity of mAb 2c in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…A number of approaches have been explored to counteract HSV‐1 infection. Notably, monoclonal antibodies have recently been developed to neutralize both circulating virions and viral transmission, 9 and an alternative strategy to block HSV‐1‐induced LG has been achieved using anti‐VEGF‐A monoclonal antibody in mice 4 . On the basis of additional new information provided by this study, 1 lymphatic‐based therapy should offer a promising new strategy to treat HSV‐1 infections.…”
mentioning
confidence: 82%
“…A number of approaches have been explored to counteract HSV‐1 infection. Notably, monoclonal antibodies have recently been developed to neutralize both circulating virions and viral transmission, 9 and an alternative strategy to block HSV‐1‐induced LG has been achieved using anti‐VEGF‐A monoclonal antibody in mice 4 . On the basis of additional new information provided by this study, 1 lymphatic‐based therapy should offer a promising new strategy to treat HSV‐1 infections.…”
mentioning
confidence: 82%
“…Humanized monoclonal antibody mAb hu2c were administered in mice and resulted in inhibition of cell-to-cell viral transmission a key mechanism by which HSV-1/2 escapes humoral immune surveillance. mAb hu2c was found to neutralize HSV fully independent of complement or/and recruit immune effector cell in a highly efficient manner [167,168]. These features guarantee the clinical development of mAb hu2c for treatment of HSV infections in drug-resistant and immunocompromised patients.…”
Section: Monoclonal Antibodiesmentioning
confidence: 93%
“…Topical treatment was carried out by periodical inoculations (five times a day) of the ipsilateral and contralateral eye with 5 μl (20 μg) of mAb 2c solution (in PBS; eye drops) started at 24 h post-infection until day 12. The antibody dose of 300 μg/injection was adjusted according to our prior studies where we demonstrated the efficacy of these antibodies in the NOD/SCID mouse model for immune deficiency ( Krawczyk et al, 2013 ) and BALB/c model for HSK ( Krawczyk et al, 2015 ). Moreover, 15 mg/kg body weight (equal to 300 μg/mouse) represents the dosage for palivizumab, the only humanized antiviral antibody (IgG1, like mAb hu2c) that was approved by the Food and Drug Administration for the reduction of serious lower respiratory tract infections caused by the respiratory syncytial virus ( Brady et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they successfully block the cell-to-cell transmission of HSV between infected and non-infected Vero cells ( Krawczyk et al, 2011 , 2013 ). Moreover, these antibodies effectively prevented mice from the development of a lethal infection in the NOD/SCID mouse model for immunosuppression ( Krawczyk et al, 2013 ) and from HSK in the corresponding mouse model ( Krawczyk et al, 2015 ). Besides generalized infections that may lead to lethal encephalitis and infections of the cornea resulting in HSK, infections of the cornea with HSV are a severe disease that urgently needs an improved therapy.…”
Section: Introductionmentioning
confidence: 99%